Performance of Red Chili Plants (Capsicum annum L.) in Response to Organic Fertilizer Mixture of Palm Oil Fronds, Empty Fruit Bunches, and Cow Manure - Sunarti; Nurseha; Aryani, Farida (Universitas Muhammadiyah Bengkulu, 2025)
Abstract. One approach to increasing chili production is through fertilisation. The use of organic fertilizers is a viable alternative. This study aims to evaluate the response of red chili plants (Capsicum annum L.) to the application of an organic fertilizer made from a mixture of palm oil fronds, empty fruit bunches, and cow manure. The research was conducted from April to July 2024 in Lubuk Sini Village, Taba Penanjung District, Central Bengkulu Regency. The method employed was an experimental one, using a Completely Randomised Design (CRD) Non-Factorial with one factor and four replications. The treatment factor was the dose of the organic fertilizer mixture of palm oil fronds, empty fruit bunches, and cow manure, comprising five levels: D0 = Without Organic Fertilizer (NPK 200 kg ha-1), D1 = 15 t h-1, D2 = 20 t h-1, D3 = 25 t h-1, and D4 = 30 t h-1. Data were analysed using analysis of variance (ANOVA), followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results showed that the D4 = 30 t h-1 dosage had a significant effect on the height and fruit weight of red chili plants. Key word: Red chili, Organic fertilizer, Palm oil fronds, and emty fruit bunches